58‐3: Development of 4 Side Narrow Border UHD Display with TopGate IGZO‐TFT and DeMUX Technology. Issue 1 (29th May 2019) - Kikuchi, Tetsuo; Hara, Kengo; Kitagawa, Hideki; Morinaga, Junichi; Ogasawara, Isao; Imai, Hajime; Daitoh, Tohru
Abstract : We have developed IGZO‐TFT with high mobility and high reliability. In this paper, we report on the development of 4 side narrow border 13.4‐inch UHD prototype display operating at 120Hz with newly developed high ON current TopGate IGZO‐TFT and DeMUX technology.